Fire spalling behavior of high-strength concrete: A critical review. (25th July 2022) - Amran, Mugahed; Huang, Shan-Shan; Onaizi, Ali M.; Murali, G.; Abdelgader, Hakim S.
Highlights: High-strength concrete (HSC) is a suitable structural concrete material for ensuring long-term durability. The major factors that lead to the explosive spalling of HSC are heating rate, moisture content, and permeability. This review provides in-depth evaluations of the behaviors and prevention of fire spalling in HSC applications. The addition of cementitious materials and fibers are part of the strategies to prevent spalling in HSC. Further efforts are needed to establish a guideline to allow the design of HSC mixtures to eliminate spalling. Abstract: Building and infrastructure damages, such as tunnels, have become a more important issue because of the continuous expansion of rural and urban constructions. It is well-known that when high-strength concretes (HSCs) are exposed to high temperatures; it is more likely to experience explosive fire-induced spalling than conventional strength concrete. Spalling might result in catastrophic loss of life and damage to nearby critical infrastructure. The exposure of reinforcement bars to elevated temperature, decreased permeability, higher density, moisture transfer, and brittleness of the HSC contribute to spalling. The concrete on a structural member's surface may be violently ripped apart by a high and fast rising temperature during a fire. Despite being a non-combustible material, the physics-chemo-mechanical properties of concrete deteriorate when subject to high temperatures. The magnitude and duration of a fire in a concrete structure define the severity of the fire. The resistance to fire spalling of HSCs under different fire conditions, extremes, and tendencies must be explored urgently. Cementitious materials exhibited a positive impact as an alternative to cement in HSC because they are known as environmentally friendly concrete materials with superior fire-resistant properties. In addition, the inclusion of fibers as an additive reinforcement is adopted to prevent and mitigate fire spalling in HSCs. Therefore, the establishment of appropriate fire-safety measures is a fundamental requirement in building design to ensure the safety of its inhabitants. While the process of fire spalling for HSC during a fire has not yet been completely understood. For this reason, a critical literature study on recent developments in HSC fire-resistance performance should be conducted to determine the present fire spalling behavior of HSC in the event of high temperatures and/or a fire. This article systematically reviews the mechanisms, influential factors, and types of fire spalling. This literature also reviews the behavior, fire spalling modelling, and strategies to prevent spalling in HSC applications. Given the advantages of the research subject, several hotspot research topics for scientific investigations are also suggested to facilitate the widespread use of HSCs in advanced construction applications.